Do Exports of Services Lengthen the Duration of Export of Goods? Evidence from Kenya - Majune, Socrates; Egwaikhide, Festus; Kiplangat, Josea (Review of Economic Analysis, 2024)
This study investigates the effect of service exports disaggregated into nine categories (transport, travel, construction, government, ICT, personal, cultural and recreational, financial, insurance, and other business services) on the survival of goods exports in Kenya. Estimates from the discrete-time probit model with random effects on bilateral trade data covering 1996 to 2019 show that export of services positively and significantly impact the duration of goods exports. A disaggregation of the goods into intermediate, consumption, capital, differentiated and homogenous products shows that transport and ICT service exports increase the duration of export of goods. Therefore, the simultaneous advancement of goods and service exports would foster the export survival of goods. In particular, the results indicate that export survival of value chain commodities would be enhanced through enhancing modes of transportation alongside communication and connectivity infrastructure. Our results also have implications for the African Continental Free Trade Area (AfCFTA) which seeks to synchronously negotiate and promote trade in goods and trade in services within Africa.